Biofortification of chervil with selenium - V. A. Kharchenko; N. A. Golubkina; A. I. Moldovan; G. Caruso (Овощи России)
Relevance. Production of functional food with high levels of antioxidant status and selenium is essential for human protection against viral and cardiovascular diseases as well as cancer.Methods. Evaluation of the efficiency in foliar sodium selenate biofortification (25. 50 and 75 mg Se/L) was achieved on three chervil genotypes.Results. Intervarietal differences in biofortification level was demonstrated: from 15.5 to 31.1 for 25 mg Se/L dose; from 36.9 to 64.6 for 50 mg Se/L dose; and from 72.9 to 130 for 75 mg Se/L dose. At the chosen doses, selenium supply did not affect significantly the yield, antioxidant properties and photosynthetic content of chervil. Total antioxidant activity was in the range from 30 to 42 mg GAE/g d.w., phenolics content from 9 to 13 mg GAE/g d.w, flavonoids from 5 to 12 mg-eq quercetin/g d.w., ascorbic acid from 33 to 66 mg/100 g fresh w. High levels of carotene were a typical feature of Se fortified and non-fortified chervil. A direct correlation was recorded between phenolics content and total antioxidant activity (r=+0.954, P<0.01), and between water soluble compounds and nitrates accumulation (r=+0.920, P<0.01). Biofortification with selenium did not affect significantly the mineral content of plants. Consumption of 100 g of fresh chervil leaves, fortified with selenium, provides from 50 to 75% of the adequate selenium consumption level and from 16 to 20% of potassium. Taking into account that both selenium and potassium normalize heart activity, the new functional food product may be recommended for prophylactics and treatment of cardiovascular diseases and for the human selenium status optimization.